2012
DOI: 10.1016/j.bbamem.2011.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Opposing roles of connexin43 in glioma progression

Abstract: Despite the tremendous amount of data over the last 40years, lack of gap junctional intercellular communication (GJIC) or altered expression of gap junction proteins is still a lesser known 'hallmark' of cancer. Expression of astrocytic gap junction protein, connexin43 (Cx43), is often reduced in astrocytomas, the most common neoplasia of the central nervous system (CNS) in adults. Supported by a number of evidences, the global decrease of Cx43 expression appears to be advantageous for the growth of glioma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 140 publications
1
99
0
3
Order By: Relevance
“…Therefore, introduction of oncogenes and mitogens to cultured cells interfere with GJIC by reducing the number of connexin-containing GJ plaques and/or alter its trafficking to the plasma membrane (Laird et al, 1995;Naus and Laird, 2010). The role of Cx43 in apoptosis is less well studied and it remains controversial whether GJIC is pro-or anti-apoptotic (Sin et al, 2012). Recent evidence suggests the hemichannel activity of Cx43 may have a more significant role than intercellular channel activity in affecting cell death Decrock et al, 2009;Retamal et al, 2006), and identification of Cx43 in mitochondria suggests GJ proteins may influence pathways linked to apoptosis control (Lu et al, 2010;Ruiz-Meana et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, introduction of oncogenes and mitogens to cultured cells interfere with GJIC by reducing the number of connexin-containing GJ plaques and/or alter its trafficking to the plasma membrane (Laird et al, 1995;Naus and Laird, 2010). The role of Cx43 in apoptosis is less well studied and it remains controversial whether GJIC is pro-or anti-apoptotic (Sin et al, 2012). Recent evidence suggests the hemichannel activity of Cx43 may have a more significant role than intercellular channel activity in affecting cell death Decrock et al, 2009;Retamal et al, 2006), and identification of Cx43 in mitochondria suggests GJ proteins may influence pathways linked to apoptosis control (Lu et al, 2010;Ruiz-Meana et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Various studies in gliomas have demonstrated a role of Cx43 in glioma growth control and migration [reviewed in (Sin et al, 2012)]. The reduction of GJIC in tumor cells is often attributed to reduced Cx43 expression (Mesnil et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it does not help for a better characterization of glioblastomas. The fact that Cx43 is still detected in high‐grade gliomas (grades III and IV) may be in favor of the presence of possibly invasive cells as glioblastoma are known to be very invasive and Cx43 has been involved in vitro in glioma migration and invasion 21, 22. Future in situ studies will determine whether Cx43 is related to in situ glioma invasion even for low‐grade tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Adjacent glioma cells physically interact via adhesion proteins, microtubes, membrane fusing, microvesicles, and by gap junctions [34][35][36][37]. Although the mechanisms by which adjacent tumor cells interact are numerous, substantial evidence indicates that gap junctions play key roles in intercellular communication, and can regulate both glioma proliferation and invasion [36,[38][39][40]. Indeed, even cell-to-cell interactions via microtubes, adherens, and microvesicles are modulated by gap junctions [34,41,42].…”
Section: Resultsmentioning
confidence: 99%